สถานการณ์และศักยภาพการพัฒนาเชื้อเพลิงชีวภาพในประเทศไทย - สุขกำเนิด, เดชรัต (Asian Journal of Applied Economics, 2013)
บทคัดย่อ การเพิ่มขึ้นของราคาน้ำมันเชื้อเพลิง ส่งผลให้มีการพัฒนาน้ำมันเชื้อเพลิงชีวภาพในประเทศไทยเป็นไปอย่างรวดเร็วจนเกิดความห่วงใยในผลกระทบที่จะเกิดขึ้นกับความมั่นคงทางอาหาร บทความนี้ทบทวนและวิเคราะห์สถานการณ์และศักยภาพการผลิตน้ำมันเชื้อเพลิงชีวภาพและวัตถุดิบ การวิเคราะห์พบว่าประเทศไทยมีศักยภาพในการผลิตเอทานอลถึงระดับร้อยละ 20 ของการใช้น้ำมันเบนซินโดยไม่ต้องเพิ่มพื้นที่เพาะปลูก แต่ปัจจุบันยังมีปัญหาโครงสร้างราคาที่ไม่จูงใจ ส่วนไบโอดีเซลมีปัญหาด้านศักยภาพวัตถุดิบและจำเป็นต้องมีการขยายพื้นที่เพาะปลูกปาล์มน้ำมัน การพัฒนาเชื้อเพลิงชีวภาพที่เป็นอยู่ในประเทศไทยยังไม่ส่งผลกระทบชัดเจนต่อการผลิตอาหารและราคาอาหาร แต่อาจจะส่งผลกระทบมากขึ้นในอนาคตอันใกล้หากมิได้มีการเตรียมการรับมือที่ดีพอ คำสำคัญ : พลังงานชีวภาพ, ความมั่นคงทางอาหาร, เอทานอล, ไบโอดีเซล Abstract The recent oil price surge has driven a rapid growth in bio-fuel development in Thailand. This has raised concerns on food security by the impact of converting plant-derived food materials into fuel. This article reviews and analyzes the status and potential of biofuels and their feedstock. The analysis shows that Thailand can increase the supply of ethanol up to 20% of gasoline consumption without expanding planted areas. However, the current price structure of ethanol makes investment into ethanol production from crops unattractive. Meanwhile, the limited feedstock is a major constraint to biodiesel development. This would require expansion in the area planted to oil palm. As yet there is no evidence that the recent biofuel development in Thailand has negative impacts on food production and prices. But without coping strategies, the impacts could become serious in the near future. Keywords : biofuel, food security, ethanol, biodiesel